2018
DOI: 10.1111/jpc.13905
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal oesophageal perforation: The role for non‐operative management

Abstract: Oesophageal perforation is severe complication secondary to instrumentation of the upper gastrointestinal tract in neonates. Prompt and accurate diagnosis is crucial. Non-operative management is effective for the majority, though morbidity is common.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 5 publications
(17 reference statements)
3
7
0
Order By: Relevance
“…6 Hodgson et al reported outcome of eleven neonates with EP and they reported that all neonates were managed with bowel rest and intravenous antibiotics for a median of 7 days; and only two patients required operative intervention. 7 In conclusion, EP is not uncommon in premature infants. Early suspicion and diagnosis of EP is important because appropriate treatment usually ensures a good outcome.…”
Section: Article Historymentioning
confidence: 84%
“…6 Hodgson et al reported outcome of eleven neonates with EP and they reported that all neonates were managed with bowel rest and intravenous antibiotics for a median of 7 days; and only two patients required operative intervention. 7 In conclusion, EP is not uncommon in premature infants. Early suspicion and diagnosis of EP is important because appropriate treatment usually ensures a good outcome.…”
Section: Article Historymentioning
confidence: 84%
“…Further, they are not useful in detecting the development of mediastinal abscess, which is one of the most serious complications of esophageal perforation. 8 Although nonoperative conservative management has consistently shown satisfactory prognosis in several case series of neonatal esophageal perforation, 3 7 9 10 11 surgical interventions are required when the abscess is formed within the mediastinum. 7 12 13 …”
Section: Discussionmentioning
confidence: 99%
“…Conservative management of oesophageal perforation is treatment of choice after removal of the gastric tube 1. The diagnosis can be confirmed using water-soluble contrast (figure 2A).…”
Section: Answers To the Questions On Pagementioning
confidence: 99%